Biomarkers in Stress Related Diseases/Disorders: Diagnostic, Prognostic, and Therapeutic Values - Dhama, Kuldeep; Latheef, Shyma K.; Dadar, Maryam; Samad, Hari Abdul; Munjal, Ashok; Khandia, Rekha; Karthik, Kumaragurubaran; Tiwari, Ruchi; Yatoo, Mohd. Iqbal; Bhatt, Prakash; Chakraborty, Sandip; Singh, Karam Pal; et al. (Frontiers in Molecular Biosciences, 2019)
Various internal and external factors negatively affect the homeostatic equilibrium of organisms at the molecular to the whole-body level, inducing the so-called state of ‘stress’. Stress affects an organism’s welfare status and induces energy-consuming mechanisms to combat the subsequent ill effects; thus, the individual may be immunocompromised, making them vulnerable to pathogens. The information presented here has been extensively reviewed, compiled and analyzed from authenticated published resources available on Medline, Pubmed, Pubmed Central, Science Direct, and other scientific databases. Stress levels can be monitored by the quantitative and qualitative measurement of biomarkers. Prominent markers of stress include thermal stress markers like heat shock proteins (HSPs), innate immune markers like Acute Phase Proteins (APPs), oxidative stress markers, and chemical secretions in the saliva and urine. In addition, stress biomarkers are thought to play critical roles in the prognosis of stress-related diseases and disorders, and in therapy guidance. Moreover, different components have been identified as potent mediators of cardiovascular, central nervous system, hepatic, and nephrological disorders, which can also be employed to evaluate these conditions precisely, but with stringent validation and specificity. Considerable scientific advances have been made in the detection, quantitation, and application of these biomarkers. The present review describes the current progress of identifying biomarkers, their prognostic and therapeutic values.